KEKERASAN VERBAL ORANG TUA TERHADAP ANAK DI DUSUN GALESONG, DESA GALESONG KOTA, KECAMATAN GALESONG, KABUPATEN TAKALAR - Hasdian Suraya; Imam Mukti; Nurdyansa (Jurnal Riset Multidisiplin Edukasi, 2025)
Verbal Violence of Parents Against Children in Dusun Galesong, Galesong Kota Village, Galesong District, Takalar Regency. (Supervised by Mr. Imam Mukti and Mr. Nurdyansa). Verbal violence is a form of violence that involves the use of harsh words spoken by parents. Verbal violence from parents to children often occurs in family environments, where it affects the child's feelings through the use of harsh words. The purpose of this study is to determine the impact of verbal violence from parents to children in Dusun Galesong and the factors that cause this verbal violence in Dusun Galesong. The method used in this study is a qualitative descriptive approach. The research findings indicate that verbal violence occurs due to economic factors. Financial instability within the family makes parents easily frustrated with their children. Due to financial pressures, continuous demands from children make parents more likely to use harsh words. Children may not understand the daily life of their parents, but discussing finances often creates tension within the family. The impact of verbal violence is also observed based on the parenting style. Parents who frequently scold their children and use harsh words will make the child become stubborn, rebellious, and unwilling to follow their parents' instructions. This is due to the use of verbal violence or commands accompanied by a harsh communication style.